Captivate 5 introduction - Connors, Lisa.; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course is designed for beginners and intermediate Adobe Captivate 5 users who want to create software demonstrations and interactive simulations. You will learn how to explore the environment; create, update, publish and organize projects; record and modify audio; and add quizzes. The course will cover how to enhance projects with animated text, highlight boxes, zoom boxes and images. Learn all this from one of the best e-learning developers in the business."--Resource description page.
Presenter, Lisa Connors.
Title from resource description page (viewed Apr. 12, 2013).
Keywords: Captivate (Electronic resource); Interactive multimedia -- Authoring programs; Presentation graphics software -- Programmed instruction; Multimedia communications -- Programmed instruction; Electronic books